Ranking Of Indonesia Sedimentary Basin And Storage Capacity Estimates For Co2 Geological Storage - Utomo P Iskandar; Sudarman Sofyan; Usman Usman (Scientific Contributions Oil and Gas, 2011)
The various possible strategies to combat global warming are explored within a wideranging of efforts. Practical solutions will need to stop or even reverse the build-up of CO2 in the environment by using existing technology that has not been integrated, carbon dioxide capture and storage (CCS) (Hansson, 2008). The main objectives of this study are to develop criteria for sedimentary basins ranking system in terms of their suitability for CO2 storage and estimate the storage capacity available. We adapt the method developed by Bachu (2003) to the Indonesia geological characteristics. Once the criteria has been developed and the basins ranked based on their suitability, oil and gas fields located within these basins were estimated their potential storage capacity using the methodology developed by Carbon Sequestration Leadership Forum (CSLF). From 60 identified sedimentary basins, Kutei, Tarakan and South Sumatera basins are respectively positioned in top three of the ranking system. Well known geological structure, adequate data, relatively stable geological structure and established infrastructures are the main factors make these basins have higher suitability. Estimation result showed from 48 fields that are considered depleted from their Np/Ult ratio (hydrocarbon cumulative production over ultimate recovery), Riau and South Sumatera region have large storage capacities which are around 229 and 144 MtCO2 respectively. The ranking of Indonesia sedimentary basins can then be used in making decisions for the large-scale implementation of CCS Project. The potential storage capacity might increase as data more available. The estimates resulted from this study is not a conclusive estimation where degree of geological and economic uncertainty associated with a capacity estimate is still high. However, from this estimation shows that Indonesia has huge potential of CO2 storage in depleted oil and gas reservoirs